(1+cscx/secx) - cotx = cosx secx + tanx = (cosx/1-sinx) (sinx/1-cosx) = (1+cosx/sinx)
Follow Math Help Forum on Facebook and Google+
Originally Posted by nichole23 (1+cscx/secx) - cotx = cosx Hi nichole23, Try posting these one at a time. I think you'd have a better chance of getting them answered. Just a suggestion.
Originally Posted by nichole23 secx + tanx = (cosx/1-sinx) Hi again nichole23, Multiply left side by
Originally Posted by nichole23 (sinx/1-cosx) = (1+cosx/sinx) Hello again, Multiply left side by
Thank you so much!!!! I really appreciate it!
View Tag Cloud